2005
DOI: 10.1111/j.1365-2214.2005.00511.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the comparative responsiveness of a core set of outcome measures in a school‐based conductive education programme

Abstract: Several strong measures of outcome were identified. Further work is needed to find valid and sensitive psychosocial and school participation measures for these young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 39 publications
1
40
0
Order By: Relevance
“…Discriminative validity: Detects differences between children with/without CP [12]. Activity domain difficult for children with CP [53]. Adequate Adequate Not established…”
Section: Excellent Excellent Excellentmentioning
confidence: 99%
“…Discriminative validity: Detects differences between children with/without CP [12]. Activity domain difficult for children with CP [53]. Adequate Adequate Not established…”
Section: Excellent Excellent Excellentmentioning
confidence: 99%
“…Wright et al reported increased parental stress after a second year of CE in an educational setting [13]. Reddighough et al reported a better outcome of parents' perception of coping for the CE-than the NDT-approach [10].…”
mentioning
confidence: 99%
“…Furthermore, the inter-rater reliability 67,73) and the test-retest . 5-point scale (-2 -+2) 0=expected level of outcome +2=much more than the expected outcome level -2=much less than the expected outcome level Each goal weighted, and T-score calculated 8,46,47) Clients/patients of mental health programs 11,48) , young children with disabilities 8,17,18,49,50) , stroke or brain injuries 21,[51][52][53] , geriatric care 54,55) ,…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, this may be considered to be an interview via free conversation, to set goals. The validity, reliability, and responsiveness of GAS has been evaluated not only in the mental health field but also in various fields such as those involving children with disabilities (e.g., cerebral palsy and mental and/or physical retardation), elderly patients, brain injury patients, dementia patients, and frail elderly people (Table 3, 4) 8, 11,17,18,[48][49][50][51][52][53][54][55][56][57][58][59][60][61] . In children with disabilities, no significant correlation was noted between the standardized measure, the Peabody Gross Motor Scale, and the GAS T-score 17,18) , which suggests that GAS determines aspects different from the Peabody Gross Motor Scale.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation